Genetic Variability, Correlation and Path-Coefficient Studies in Litchi (Litchi chinensis Sonn.) for Plant Growth, Panicle and Yield Attributes - Lal, Narayan; Singh, Awtar; Kumar, Abhay; Marboh, E. S.; Gupta, A. K.; Pandey, S. D.; Nath, Vishal (International Journal of Bio-resource and Stress Management, 2022)
Studies were carried out in National Active Germplasm Site (NAGS) at ICAR-NRC on Litchi, Muzaffarpur, Bihar, India during 2018 and 2019 to find out the association between different characters and magnitude of association of different characters with yield (kg plant-1) in nine clones of litchi (Litchi chinensis Sonn.). Result revealed that genotypic coefficient were higher than their corresponding phenotypic ones implying an inherent relationship among them. The differences between genotypic and phenotypic coefficient of variation (PCV and GCV) were found narrow for all traits indicate least influence of environment on traits. Heritability was more than 80% for all the parameters studied except seed weight (34.90%) and TSS (73.20%). Correlation analysis quantifies only the degree of association between two characters and non-significant correlation coefficient value cannot be taken to imply absence of functional relationship between the two variables but path coefficient analysis reveals this by breaking the total correlation coefficient into components of direct and indirect effects. The number of leaflet, leaf length, leaf width, rachis length, petiole length, length of panicle, fruit weight, pulp weight, TSS, total sugar and seed weight exhibited positive correlation. Among the character studied, leaf length (1.646), TSS (0.975), length of panicle (0.900), petiole length (0.639), and number of fruit per panicle (0.601), seed weight (0.465) and pulp weight (0.370) recorded maximum positive direct effect towards yield at both the level. This study revealed that leaf length, panicle length, number of fruit per panicle and seed weight could form a selection criterion for yield improvement in litchi.